Restoration of endodontically treated teeth - Gonzaga, Carla Castiglia; Campos, Edson Alves de [UNESP]; Baratto Filho, Flares (My University, 2011)
The restoration of endodontically treated teeth is one of the most challenging situations of the dentist`s clinical practice, because it involves procedures related to several areas, such as Endodontics, Operative Dentistry, and Prosthetics. These restorations aim to replace the structures lost during endodontic surgery and access to both the pulp chamber and root canal system during the instrumentation, as well as the removal of the carious tissue and temporary restorations. It is also important to remember that the prognosis of endodontically treated teeth depends not only on endodontic treatment success itself, but also on the amount of remnant tooth tissue and the definitive restoration that will be placed onto the dental element.
Keywords: Intraradicular posts; Endodontically treated teeth; Restoration